Geometric numeric integration in the event-driven measurement method - Simonov, Mikhail (2016 Second International Conference on Event Based Control, Communication, and Signal Processing (EBCCSP), 2016)
The Event-Driven Metering (EDM) method is about data-driven compression of the measurement data based on the replacement of the original arbitrary shape of the load by a simplified polygonal line that represents the same values of the energy per interval of time. EDM algorithm receives the Shannon data samples encoding the local measurements and reports the pre-processed knowledge to the controlling hosts in the form of Lebesgue-based events. This article explains the mathematical foundations of the invention that allows improved data efficiency. Method decomposes the global behavior of an energy system in a sequence of linearized chunks and exploits the energy conservation law in order to set up data-driven geometric integration. The result is an operator that maps a load shape into a data-efficient sequence of tokens representing exactly the same energy quantities as in the original pattern.